Programa Devolve ICMS do Estado do Rio Grande do Sul (ICMS Personalizado): reconstrução normativa do princípio da capacidade contributiva no alcance da justiça social, conforme abordagem complementar das concepções de justiça de John Rawls e de Amartya Sem - Braga, Thécio Antônio Silveira (2022)
This study deals with the measure of justice in personalizing tax taxation ICMS, in order to relate the subjectivity of the final consumer with the personal nature of the principle of contributory capacity, as implemented by the State of Rio Grande do South (RS) at the end of 2021, through the Devolve ICMS program. In this sense, the theme of research is the achievement of social justice through tax justice. The problem explored it was the injustice of a family benefiting from the União Auxílio Brasil social program to contribute for public financing indirectly (in fiscal regression) with the same tax burden than any other family when consuming the same foodstuffs. Such problematic was developed through a bibliographical and data review open governments, based on exploratory research with a hypothetical-deductive approach, now hypothetical-inductive, with the purpose of verifying whether the taxation hypothesis personalized ICMS is fairer than the equal taxation of the current tax predominantly in the country, whose protection of the existential minimum is operationalized exclusively by the institutes of selectivity and essentiality. To this end, initially we explored the differences between John Rawls and Amartya Sen's conceptions of justice in order to highlight the complementary nature of these theories. Following, some injustices in the equal ICMS taxation in relation to the consumption of families with different capabilities economic. Afterwards, the complementary approach to Rawlsian school lessons was discussed, and Senian in the process of normative reconstruction of the principle of capacity implemented by the State of RS and tested whether personalized ICMS is a better justice solution than the peer selectivity/essentiality. Finally, it was concluded that the Devolve ICMS program protects effectively part of the income distributed by the Union used in the consumption of the effects tax regressives. Therefore, it made tax taxation in the State of RS fairer (equitable) and in favor of achieving social justice in the country.